2009
DOI: 10.1016/j.ejcts.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative chest tube management: measuring air leak using an electronic device decreases variability in the clinical practice☆☆☆

Abstract: We have demonstrated a high rate of disagreement related to the indication to remove chest tubes after lung resection and the improvement of the agreement rate with the use of an electronic device to measure postoperative air leak and pleural pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 15 publications
(13 reference statements)
4
82
0
4
Order By: Relevance
“…Previously published reports have demonstrated that digital drainage systems are superior in reducing the incidence of post-operative prolonged air leak (12)(13)(14). Several articles describe the advantage of a digital system in eliminating the inter-observer differences related to air leak grading, as the system quantifies the precise amount of air leak (13)(14)(15). Moreover, the effect of continuous vs. intermittent suction on postoperative air leak may also account for differences in air leak duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published reports have demonstrated that digital drainage systems are superior in reducing the incidence of post-operative prolonged air leak (12)(13)(14). Several articles describe the advantage of a digital system in eliminating the inter-observer differences related to air leak grading, as the system quantifies the precise amount of air leak (13)(14)(15). Moreover, the effect of continuous vs. intermittent suction on postoperative air leak may also account for differences in air leak duration.…”
Section: Discussionmentioning
confidence: 99%
“…To date, drainage systems have only been compared with relation to postoperative air leak (11)(12)(13)(14)(15). Whilst this is an important aspect of the decision to remove chest tubes, the volume of fluid extracted is another major determinant, that continues to garner increased attention amongst research circles (2,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…An initial survey of patients and nurses on the use of the portable device has already produced preliminary confirmation that chest drain handling and patient mobility are improved compared to conventional water seal systems . Perhaps more importantly, it has also been shown that use of the digital air flow monitor on a digital system such as the Thopaz can accurately and objectively measure post-operative air leaks after lung surgery (Varela et al, 2009). A study from Hong Kong has already demonstrated that the greater consistency in monitoring air leaks can be translated into more decisive, confident post-operative chest drain management resulting in shortened chest drain durations and lengths of hospital stay (Yeung & Sihoe, 2010).…”
Section: Future Directionsmentioning
confidence: 99%
“…It objectifies much of the subjective information and can be replicated among several observers (9). The level of agreement significantly increased in nurses, surgeons and residents (11,(13)(14)(15). This system enables the health care team, regardless of their experience or level of education, to accurately report the status a patient's air leak (9,14).…”
Section: Interobserver Variabilitymentioning
confidence: 99%